Неозапозичення в українському футбольному інтернет-дискурсі - Максимчук, Віталій (Slavia Centralis, 2020)
The paper focuses on the analysis of the new borrowed words in modern Ukrainian football Internet discourse. Using different criteria such as lexicographic, chronological, functional and semantic, the author describes Spanish, Italian, English, German and other new borrowed words. Spanish and Italian innovations are the national identifiers, but sometimes they gain generalized semantics. English new borrowed words name the functions of football players in the field, types of ball kicks, time periods, etc. In Ukrainian football Internet discourse new borrowed words compete on grammar, orthographic and graphic levels, but those innovations that do not contradict current linguistic standards prevail. However, lexical competitors peacefully coexist, expanding synonymous rows of the Ukrainian language.